Perubahan Komunikasi Masyarakat Dalam Inovasi Mitigasi Bencana di Wilayah Rawan Bencana Gunung Merapi - Damayanti Wardyaningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This study aims to analyze changes in communications in disaster mitigation innovation in communication of society in disaster-prone areas with the events of Mount Merapi eruption in 2010. The method used is descriptive research data collection through observation and interviews with community territory in the hamlet Kalitengahkidul, Glagaharjo village, Sleman, Yogyakarta. The concept used is the diffusion of innovation, information and disaster mitigation. The results showed there were adoption of innovations related to the disaster mitigation community communication. Communication changes occur in the communication tools used, sources of information to determine the evacuation decision making, communication, community groups define the disaster mitigation procedures, sources of information about volcanic activity and the priority that must be performed during emergency response and post-disaster recovery period. Findings of the study after the eruption of 2010 appears attitude residents of disaster-prone region more independent and have the initiative in adopting innovations disaster mitigation, especially in terms of communication among communities in the face of potential disasters that will arise.